Dating igneous rocks using the Potassium–Argon Laser Experiment (KArLE) instrument: A case study for ~380 Ma basaltic rocks. (11th September 2018) - Cho, Yuichiro; Cohen, Barbara A.
Abstract : Rationale: We report new K–Ar isochron data for two ~380 Ma basaltic rocks, using an updated version of the Potassium–Argon Laser Experiment (KArLE), which is being developed for future in situ dating of planetary materials. These basalts have K contents comparable with those of lunar KREEP basalts or igneous lithologies found by Mars rovers, whereas previous proof‐of‐concept studies focused primarily on more K‐rich rocks. We aim to measure these analogous samples to show the advancing capability of in situ K–Ar geochronology. Methods: Combining laser‐induced breakdown spectroscopy (LIBS), mass spectrometry (MS), and microscopic analyses, we measured the abundance of K and 40 Ar from 23 spots on the basalt samples. We then constructed K–Ar isochron plots from these rocks. The breadboard instrument consists of flight‐equivalent devices including a 30‐mJ Nd:YAG laser and a quadrupole mass spectrometer. Results: Despite much lower K abundances than in previous studies, the isochron slopes yielded 380 ± 44 Ma and 398 ± 50 Ma for 380.7‐Ma and 373.5‐Ma rocks, respectively, indicating that accuracy better than 25 Ma (<7%) is achievable with our instrument. The isochron intercepts both yielded trapped 40 Ar approximately 1 × 10 −6  cm 3 STP/g. Conclusions: Our experimental results demonstrate that accurate and precise measurements are possible using the KArLE approach on basaltic rocks, which are ubiquitous on planetary surfaces, and are useful in addressing a wide range of questions in planetary science.